Binary Star Orbits. VI. The Interferometric-spectroscopic Binary 73 Leo - Brian D. Mason; R. Elizabeth M. Griffin; R. T. Zavala; Christian A. Hummel; Haley M. Hurowitz; Jonathan L. Hurowitz; William I. Hartkopf; Ellyn K. Baines; Stephen J. Williams; Rachel A. Matson (The Astronomical Journal, 2025)
Discordances in radial-velocity measurements of 73 Leonis, made more than a century ago, gave rise to the first suggestion that this fifth-magnitude star was a binary system, but it was 40 yr before an accurate investigation of the object commenced, and a further 25 yr (close to three orbital cycles) before R. F. Griffin’s new velocities, combined with older ones, yielded a high-quality orbit. However, a few years earlier the system had been resolved astrometrically by speckle interferometry, so a combined solution was attempted that yielded a very precise period ( σ  ∼  0.1% P , primarily on the strength of the precision of the radial-velocities), with a less-well determined semimajor axis ( σ  ∼  2.4% a ″). Nonetheless 73 Leo continued to present a challenge to astrometric and photometric techniques alike, and also to spectroscopic classification and stellar-evolution theory. Now, with the superior resolution capability of the Navy Precision Optical Interferometer and new radial-velocity data from the Dominion Astrophysical Observatory high-resolution spectrograph, those uncertainties have been reduced to 0.02% in P and 0.15% in a ″. This paper describes the new data acquired since 1997, and reports our new attempts to parameterize the system (including the spectral type of the secondary) by appealing to very recent photometry. Notwithstanding, direct spectroscopic evidence of the secondary component is little more than suggestive, so a complete SB2 solution yielding an orbital parallax and limits to the masses of the component stars remains elusive.